THE EFFECT OF A PHARMACIST COUNSELING TOWARD THE ACHIEVEMENT OF THERAPY TARGET ON HYPERTENSION OUTPATIENTS OF RSUD SARAS HUSADA PURWOREJO - Wasilin Wasilin; Zullies Ikawati; I Dewa Putu Pramantara S (Faculty of Pharmacy, Universitas Gadjah Mada)
Hypertension is a chronic disease, so patients with hypertension during his life always takes medication to control blood pressure. If blood pressure is not controlled it will result in a blood vessel complications, coronary heart disease, cardiac infarction, stroke and renal failure. The research has been conducted to determine the effect of a pharmacist counseling target blood pressure < 140/90 mmHg in hypertension patients non-diabetes mellitus and < 130/80 mmHg in hypertension patients with diabetes mellitus who was treated at the outpatients of Saras Husada Purworejo General Public Hospital. Retrieved 94 subjects of research, grouped randomly into intervention group (received counseling pharmacist) are 48 subjects and the control group (no counseling pharmacist) as many as 46 subjects. Data analysis using the Statistics Program for Social Science (SPSS). The results showed that a pharmacist counseling had a significant effect toward the achievement target of < 140/90 mmHg blood pressure on the non-diabetes mellitus hypertension patients (p = 0.000) and < 130/80 mm Hg on the hypertension patients with diabetes mellitus (p = 0.001). Key words : pharmacist counseling, non-diabetes mellitus hypertension, hypertension with diabetes mellitus, decreasing of blood pressure, and the achievement blood pressure target.